Dayak Ngaju Traditional Marriage, Central Kalimantan: Concept and Juridical Review - Agung Aditya; Cahya Wulandari; Fajar Dian Aryani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
This study aims to provide an explanation of the marriage system that exists in the Dayak Ngaju tribe, Central Kalimantan, and to explain that the Dayak Ngaju tribe has redundant customary institutions that have been recognized in the Regional Regulation of Central Kalimantan Province Number 16 of 2008 concerning Central Kalimantan Dayak Customary Institutions. Traditional marriages carried out by the community are used as a cultural characteristic of the Ngaju Dayak people, the existence of a Dayak Traditional Institution can strengthen traditional marriage because Dayak Traditional Institutions have rules and conditions that must be fulfilled by both men and women. If the rules or conditions are violated later will be obliged to pay a material fine. The purpose of holding a marriage agreement because it is to maintain the preservation of customs so that no divorce occurs. Because basically in all religions divorce is prohibited in a marriage, and the existence of a marriage agreement can be used as a guideline in a household so that they have the fear of not easily carrying out a divorce, because, in the marriage agreement, the parties must carry out the contents of the marriage agreement one way or another. parties must be able to pay the fine or singer